GROWTH AND YIELD RESPONS SWEET MAIZE YIELDS TOWARDS THE APPLICATION OF OIL PALM BUNCH ASH AND NPK FERTILIZER ON ALUVIAL LAND - Leonard Raka Pambela; Mulyadi Safwan; Nurjani . (Fakultas Pertanian Universitas Tanjungpura, 2020)
The aim of this research is to find out the dose of oil palm bunch ash and NPK fertilizer which gives the best growth and yield of sweet maize plants in alluvial soil and to know the interaction between both. This research was conducted in Desa Kuala, Kecamatan Mega Timur Kabupaten Kubu Raya. This research was conducted from November 1st 2018 to Februari 1st 2019. The design used in this study was a factorial design with a Randomized Block Design (RBD) pattern. The treatment consisted of 2 factors, that is the distribution of oil palm bunch ashes (a) consisting of 2 levels of treatment and NPK fertilizer (k) consisting of 3 levels of treatment. Each treatment was repeated 5 times, so that there were 30 plots with 2 m x 1 m plot area. The treatment in question consists of the treatment of oil palm bunch ash that is a1 = palm bunch ash 2 tons / ha, a2 = palm bunch ash 4 tons / ha and NPK fertilizer treatment that is k1 = NPK fertilizer 400 kg / ha, k2 = 500 kg NPK fertilizer / ha and k3 = 600 kg / ha NPK fertilizer. The results of this study indicate that the treatment of oil palm bunch ash significantly influences the length of cob without cornhusk, while the NPK fertilizer treatment significantly influences plant height of 6 MST, root volume, plan dry weight, cob cornhusk weight, cob without cornhusk weight and diameter of cob without cornhusk. The interaction of the two treatments did not significantly affect all observed variables. The combination of oil palm bunch ash with a dose of 2 tons / ha and NPK fertilizer of 600 kg / ha save the highest mean of growth and yield of sweet maize plants in alluvial soils. Keywords : Oil palm bunch ash, alluvial land, sweet maize, NPK fertilizer